Characterizing Cross-Culturally Relevant Metrics of Stigma Among Men Who Have Sex With Men Across 8 Sub-Saharan African Countries and the United States - Augustinavicius, Jura L (Am J Epidemiol, 2020)
Overcoming stigma affecting gay, bisexual, and other men who have sex with men (MSM) is a foundational element of an effective response to the human immunodeficiency virus (HIV) pandemic. Quantifying the impact of stigma mitigation interventions necessitates improved measurement of stigma for MSM around the world. In this study, we explored the underlying factor structure and psychometric properties of 13 sexual behavior stigma items among 10,396 MSM across 8 sub-Saharan African countries and the United States using cross-sectional data collected between 2012 and 2016. Exploratory factor analyses were used to examine the number and composition of underlying stigma factors. A 3-factor model was found to be an adequate fit in all countries (root mean square error of approximation = 0.02–0.05; comparative fit index/Tucker-Lewis index = 0.97–1.00/0.94–1.00; standardized root mean square residual = 0.04–0.08), consisting of “stigma from family and friends,” “anticipated health-care stigma,” and “general social stigma,” with internal consistency estimates across countries of α = 0.36–0.80, α = 0.72–0.93, and α = 0.51–0.79, respectively. The 3-factor model of sexual behavior stigma cut across social contexts among MSM in the 9 countries. These findings indicate commonalities in sexual behavior stigma affecting MSM across sub-Saharan Africa and the United States, which can facilitate efforts to track progress on global stigma mitigation interventions.